A Review of the Ongoing Research on Zika Virus Treatment - Silva, Suely da [UNESP]; Silva Martins, Daniel Oliveira [UNESP]; Gomes Jardim, Ana Carolina [UNESP] (Mdpi, 2018)
The Zika fever is an arboviral disease resulting from the infection with Zika virus (ZIKV). The virus is transmitted to humans by the bite of Aedes mosquitos, mainly Aedes aegypti and Aedes albopictus. ZIKV has been detected for decades in African and Asian regions and, since 2007, has spread to other continents; among them, infections are most reported in the Americas. This can be explained by the presence of vectors in highly populated and tropical regions where people are susceptible to contamination. ZIKV has been considered by the World Health Organization a serious public health problem because of the increasing number of cases of congenital malformation and neurological disorders related to its infection, such as microcephaly, Guillain-Barre syndrome, meningoencephalitis, and myelitis. There is no vaccine or specific antiviral against ZIKV. The infection is best prevented by avoiding mosquito bite, and the treatment of infected patients is palliative. In this context, the search for efficient antivirals is necessary but remains challenging. Here, we aim to review the molecules that have been described to interfere with ZIKV life cycle and discuss their potential use in ZIKV therapy.
Keywords: Zika fever; ZIKV; treatment; antiviral; screen of drugs